Pemetaan Tingkat Rawan Banjir Dan Keterpaparan Permukiman Das Wae Apu Kabupaten Buru - Pasha, Fidyah Ayu; Nanlohy, W D; Puturuhu, Ferad (Jurnal Geografi, Lingkungan dan Kesehatan, 2023)
Wae Apu River is one of the rivers in Buru with a length of 47.25 km with a watershed area covering 2 districts namely Buru and South Buru with an area of 188,511 Ha. Every year the Wae Apu River overflows and causes flooding in the surrounding areas along the river channel. The cause of flooding for this river itself is influenced by 2 factors, namely natural and artificial factors (human activities). The intensity of flooding that often occurs certainly has an impact and loss for the community. Based on the existing conditions, it is necessary to conduct research related to the identification of flood-prone areas in the watershed by mapping vulnerable areas and creating settlement exposure zones which are the most at-risk components. The data analysis method used in this research is the spatial analysis and overlay method, used to provide an overview of the physical environment, flood characteristics and land use using maps in the Wae Apu watershed where each parameter will be given a weight / value depending on the level of importance of each parameter and will be overlaid to get the results of vulnerability. Based on the results of the research, the low flood vulnerability level in the Wae Apu watershed has the largest area of 133,994.7 Ha or equivalent to 73% of the total mapped area. The moderate flood prone class with an area coverage of 49,505.19 Ha or 26%. While areas with high flood vulnerability with an area of 5,011.59 Ha or equivalent to 3% of the area make this class the smallest. Residential areas exposed to moderate flood prone areas of the Wae Apu watershed are around 3,261 Ha or 90.7% and 335.84 Ha or 9.3% of residential areas are located in high flood prone areas